2017
DOI: 10.1111/imj.13451
|View full text |Cite
|
Sign up to set email alerts
|

Targeting low‐density lipoprotein cholesterol with PCSK9 inhibitors

Abstract: Over the past quarter century, clinical trials have consistently demonstrated that lowering levels of low-density lipoprotein cholesterol (LDL-C) with statins reduces the rate of major adverse cardiovascular events. However, the findings that many patients continue to experience events or harbour inappropriately high LDL-C levels despite intensive statin therapy and the clinical reality of statin intolerance suggests that additional therapeutic strategies are required in order to achieve more effective reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Identified as the ninth member of the proteinase K subfamily of subtilases, proprotein convertase subtilisin/kexin type 9 (PCSK9) is one of the most exciting new targets in cholesterol metabolism to emerge since the identification of 3‐hydroxy‐3‐methyl‐glutaryl‐CoA reductases. In its primary role, PCSK9 binds to and induces degradation of the low‐density lipoprotein receptor (LDLR), particularly in the liver, resulting in diminished hepatic clearance and increased plasma concentration of low‐density lipoprotein cholesterol (LDL‐C) . Additional roles for PCSK9 in lipoprotein metabolism and in extra‐hepatic tissues have also been identified …”
Section: Introductionmentioning
confidence: 99%
“…Identified as the ninth member of the proteinase K subfamily of subtilases, proprotein convertase subtilisin/kexin type 9 (PCSK9) is one of the most exciting new targets in cholesterol metabolism to emerge since the identification of 3‐hydroxy‐3‐methyl‐glutaryl‐CoA reductases. In its primary role, PCSK9 binds to and induces degradation of the low‐density lipoprotein receptor (LDLR), particularly in the liver, resulting in diminished hepatic clearance and increased plasma concentration of low‐density lipoprotein cholesterol (LDL‐C) . Additional roles for PCSK9 in lipoprotein metabolism and in extra‐hepatic tissues have also been identified …”
Section: Introductionmentioning
confidence: 99%
“…Proprotein convertase subtilisin/kexin type 9 (PCSK9) was discovered in 2003 and plays an important role in the regulation of lipid metabolism. 9 PCSK9 is a factor, synthesised within the hepatocyte and secreted into the circulation, where it binds to the complex between LDL particles and the LDL receptor. Within the hepatocyte, the presence of PCSK9 prevents dissociation of the LDL particle from the receptor, which directs both to lysosomal degradation.…”
Section: Pcsk9 and Lipid Homeostasismentioning
confidence: 99%
“…hypercholesterolaemia. 10 In addition, a number of polymorphisms have been identified that result in reduced PCSK9 and are associated with both lower LDL-C levels and lower rates of cardiovascular events. 11,12 Mendelian randomisation studies have provided further evidence linking low levels of PCSK9 activity with both lower lipid levels and cardiovascular risk.…”
Section: Pcsk9 and Lipid Homeostasismentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) against proprotein convertase subtilisin/kexin type 9 (PCSK9) have become the focus of much research in recent years as a new approach to lipid management . PCSK9 binds to the low‐density lipoprotein (LDL) receptor leading to its degradation, which results in an increase in circulating levels of LDL‐cholesterol (LDL‐C) .…”
mentioning
confidence: 99%